Femoral nailing associated with bone marrow emboli in pigs induced a specific increase in blood IL-6 and broad inflammatory responses in the heart and lungs - Kristiansen, Steinar; Storm, Benjamin Stage; Emblem, Åse Eeg; Grønli, Renathe Henriksen; Pettersen, Kristin; Hilmo, Jonas; Jarmund, Anders Hagen; Leth-Olsen, Martin; Nyrnes, Siri Ann; Nilsen, Bent Aksel; Nielsen, Erik Waage; Mollnes, Tom Eirik (Frontiers in Immunology, 2024)
Background. Bone marrow embolization may complicate orthopedic surgery, potentially causing fat embolism syndrome. The inflammatory potential of bone marrow emboli is unclear.We aimed to investigate the inflammatory response to femoral intramedullary nailing, specifically the systemic inflammatory effects in plasma, and local tissue responses.Additionally, the plasma response was compared to that following intravenous injection of autologous bone marrow.Methods. Twelve pigs underwent femoral nailing (previously shown to have fat emboli in lung and heart), four received intravenous bone marrow, and four served as sham controls. Blood samples were collected hourly and tissue samples postmortem. Additionally, we incubated bone marrow and blood, separately and in combination, from six pigs in vitro. Complement activation was detected by C3a and the terminal C5b-9 complement complex (TCC), and the cytokines TNF, IL-1β, IL-6 and IL-10 as well as the thrombin-antithrombin complexes (TAT) were all measured using enzyme-immunoassays.Results. After nailing, plasma IL-6 rose 21-fold, compared to a 4-fold rise in sham (p=0.0004).No plasma differences in the rest of the inflammatory markers were noted across groups.However, nailing yielded 2-3-times higher C3a, TCC, TNF, IL-1β and IL-10 in lung tissue compared to sham (p<0.0001-0.03). Similarly, heart tissue exhibited 2-times higher TCC and IL-1β compared to sham (p<0.0001-0.03). Intravenous bone marrow yielded 8-times higher TAT than sham at 30 minutes (p<0.0001). In vitro, incubation of bone marrow for four hours resulted in 95-times higher IL-6 compared to whole blood (p=0.03).A selective increase in plasma IL-6 was observed following femoral nailing, whereas lung and heart tissues revealed a broad local inflammatory response not reflected systemically. In vitro experiments may imply bone marrow to be the primary IL-6 source.